2015
DOI: 10.1039/c5ra11876j
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine-loaded functionalized mesoporous MCM-41 poly(methylmethacrylate) based composites with Candida antibiofilm activity

Abstract: The complete or partial dentures made of acrylic resins or composites constitute the support for Candida biofilm with consequent onset of stomatitis and candidiasis. In this paper polymethylmethacrylate composites containing chlorhexidine are prepared. The drug was loaded inside the mesopores of the silicate MCM-41 which had been properly silanized with an acrylic coupling agent. Four different chlorhexidine loaded composites were prepared using MCM-41 silanized with four different amounts of 3-methacryloxypro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Various mesoporous structures have been developed for the delivery of ions and drugs with applications in dentistry. Ambrogi et al [ 27 ] loaded chlorhexidine on functionalized mesoporous MCM-41 nanoparticles and prepared poly(methylmethacrylate) based composites with Candida antibiofilm activity, while Yan et al [ 28 ] used chlorhexidine-encapsulated mesoporous silica as a modifier of a commercial dental adhesive. Lu et al [ 29 ] reported that the dual-controlled release of chlorhexidine and silver ions from biodegradable mesoporous silica nanoparticles was effective against S. mutans, suggesting their potential use as nanoantiseptics for oral biofilm therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Various mesoporous structures have been developed for the delivery of ions and drugs with applications in dentistry. Ambrogi et al [ 27 ] loaded chlorhexidine on functionalized mesoporous MCM-41 nanoparticles and prepared poly(methylmethacrylate) based composites with Candida antibiofilm activity, while Yan et al [ 28 ] used chlorhexidine-encapsulated mesoporous silica as a modifier of a commercial dental adhesive. Lu et al [ 29 ] reported that the dual-controlled release of chlorhexidine and silver ions from biodegradable mesoporous silica nanoparticles was effective against S. mutans, suggesting their potential use as nanoantiseptics for oral biofilm therapies.…”
Section: Introductionmentioning
confidence: 99%
“…MCM-41 was properly silanized and the formation of silanized MCM-41 was verified by FT-IR spectroscopy. FT-IR spectrum (Figure S1) of silanized MCM-41 revealed a band at 1636 cm –1 due to the stretching vibration of the CC bond in γ-MPS and a band at 1702 cm –1 , relative to the CO stretching frequency.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Samples were prepared by grounding the specimen with KBr and spectra were obtained with 100 scans at a resolution of 1 cm –1 . To determinate the percentage of unreacted double bonds, the absorbance intensities of the methacrylate CC peak at 1640 cm –1 and of the unchanging CO peak from the ester group at 1720 cm –1 were calculated before and after polymerization ,, using a baseline method. The DC was calculated using the following formula: Where P 1 is the peak area of CC methacrylate peak and P 2 is the peak area relative to the CO of the ester group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations